New Radiocarbon Dates from CA-CCO-138 (Hotchkiss Mound) and CA-CCO-139 (Simone Mound) and Insights into Mounds, Settlement Patterns, and Culture History in the California Delta. (2nd January 2019) - Eerkens, Jelmer W.; Bartelink, Eric J.
ABSTRACT: We report 91 new AMS radiocarbon dates on human bone collagen from two important central California sites: CA-CCO-138 (Hotchkiss Mound; n = 46) and CA-CCO-139 (Simone Mound; n = 45). The sites lie within 500 m of one another in the California Delta and have figured prominently in the formulation of culture historical sequences in central California. The new AMS dates show that the two sites are nearly separate in their occupation sequences, with CA-CCO-139 interments dating between 1, 190 and 790 cal BP and CA-CCO-138 between 810 and 150 cal BP (median date ranges). We compare the new dates to previous age assignments based on associated artifacts and depth, and discuss implications for understanding ancient settlement patterns, mound occupation sequences, and culture history in the region.